The many facets of distance and space: the mobility of actors in globally distributed project teams - Clear, Tony; Hussain, W; MacDonell, SG (IEEE Computer Society Press, 2012)
Global software development practices are shaped by the challenges of time and 'distance', notions perceived to separate sites in a multi-site collaboration. Yet while sites may be fixed, the actors in global projects are mobile, so distance becomes a dynamic spatial dimension rather than a static concept. This empirical study applies grounded theory to unpack the nature of mobility within a three site globally distributed team setting. We develop a model for mapping the movements of team members in local and global spaces, and demonstrate its operation through static snapshots and dynamic patterns evolving over time. Through this study we highlight the complexity of 'mobility' as one facet of 'space' in globally distributed teams and illuminate its tight coupling with the accompanying dimensions of accessibility and context awareness.
Keywords: Distance; Global software development; Globally distributed teams; Mobility; Space